2018
DOI: 10.1075/japc.00003.yus
|View full text |Cite
|
Sign up to set email alerts
|

Managing diversity in higher education

Abstract: Situated in the first stage of Lewin’s Change Management Model (Lewin, 1947), this study examined the strategic communication plan needed to enable Higher Educational Institutions (HEIs) to embrace learner diversity via diversity engagement. Participants were 56 academics from 14 public and two private universities in Malaysia who attended the Learner Diversity training module at the Higher Education Leadership Academy (AKEPT) between the periods from 2014 to 2015. During the training sessions, participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…On the one hand, it facilitates exchange and relationships with internal publics (Melewar et al, 2018; Overton-de-Klerk; Sienaert, 2016; Simancas-González; García-López, 2017; Eger et al, 2020;Uslu, 2018). On the other, it allows establishing an important interaction with the university's external publics, such as the different members of the social, cultural, political, and economic environment (Marino;Lo-Presti, 2018;Edmiston-Strasser, 2009;Yusof et al, 2018).…”
Section: Universities' Digital Institutional Communicationmentioning
confidence: 99%
“…On the one hand, it facilitates exchange and relationships with internal publics (Melewar et al, 2018; Overton-de-Klerk; Sienaert, 2016; Simancas-González; García-López, 2017; Eger et al, 2020;Uslu, 2018). On the other, it allows establishing an important interaction with the university's external publics, such as the different members of the social, cultural, political, and economic environment (Marino;Lo-Presti, 2018;Edmiston-Strasser, 2009;Yusof et al, 2018).…”
Section: Universities' Digital Institutional Communicationmentioning
confidence: 99%
“…Similarly, a case study of Dutch students also revealed that teacher performance influences student achievement and that this influence is more pronounced for non-western students (Middlekoop, Ballafkih, & Meerman, 2017). Thus, lecturers not only need to be aware of the problems associated with diversity but also make necessary modifications to their teaching techniques to accommodate students of diverse backgrounds (Yusof, Awang-Hashim, Valdez, & Yaacob, 2018). Insensitivity to these issues may lead to inequality subsequently undermine the potential learning that can occur among diverse peers.…”
Section: Related Studies On Diversitymentioning
confidence: 99%
“…The specifics of the bottom-up approach implementation depend on the particular aspects of higher education in question: teaching, education, and the integral development of the individual in the paradigm of professional development (Yusof et al, 2018;Warr Pedersen et al, 2017). Thus, bottom-up teaching is predominantly instructor driven and is focused on separate details of teaching the discipline, implying detailing as a way of decoding and simplifying each component through repetition and memorization (Quain, 2018).…”
Section: Introductionmentioning
confidence: 99%